2022
DOI: 10.1097/mao.0000000000003579
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Tinnitus and Hypertension: A Cross-Sectional Analysis of the National Health and Nutrition Examination Survey

Abstract: ObjectiveEvaluating the association between arterial hypertension and tinnitus while controlling for gender, race, diabetes, hearing loss, and depression as potential confounders.Study DesignThe present study employed a cross-sectional design.SettingHealth interviews were conducted in the respondents’ homes.PatientsRespondents represent a nationwide sample of the noninstitutionalized civilian population of the United States. A total of 5,735 adults were identified by the NHANES 2015 to 2016 questionnaires.Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…We obtained a significant association between tinnitus and hypertension in young adults. These findings are consistent with a recent study using the NHANES database that showed a significant association between bothersome tinnitus and hypertension in young adults [ 69 ]. We observed significant tinnitus associations with scarlet fever, malaria, and meningitis, but these associations should be interpreted with caution because only a small number of participants reported these conditions.…”
Section: Discussionsupporting
confidence: 93%
“…We obtained a significant association between tinnitus and hypertension in young adults. These findings are consistent with a recent study using the NHANES database that showed a significant association between bothersome tinnitus and hypertension in young adults [ 69 ]. We observed significant tinnitus associations with scarlet fever, malaria, and meningitis, but these associations should be interpreted with caution because only a small number of participants reported these conditions.…”
Section: Discussionsupporting
confidence: 93%
“…The common risk factors for the COVID-19 and COVID-19 vaccination-related tinnitus suggest that they might share some common mechanisms. Tinnitus is generally associated with hypertension, diabetes and obesity ( Gibrin, Melo and Marchiori, 2013 ; Yang, Ma, Zheng, Yang and Lin, 2015 ; Figueiredo, Azevedo and Penido, 2016 ; Mousavi, Sajadinejad, Khorsandi and Farhadi, 2021 ; Ameen et al, 2022 ; Patel et al, 2022 ; Ramatsoma and Patrick, 2022 ; Özbey-Yücel and Uçar, 2023 ). Further studies are needed to determine whether these metabolic disorders interact synergistically with COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%